231k views
0 votes
Please help! I struggle with math so much! Can someone please explain! (2x−6)+4(x−3) =

2 Answers

4 votes

Answer:

the answer is 6x-18

Explanation:

User Juliette Dupuis
by
4.9k points
4 votes

Answer:

x = 3

Explanation:

Simplifying

(2x + -6) + 4(x + -3) = 0

Reorder the terms:

(-6 + 2x) + 4(x + -3) = 0

Remove parenthesis around (-6 + 2x)

-6 + 2x + 4(x + -3) = 0

Reorder the terms:

-6 + 2x + 4(-3 + x) = 0

-6 + 2x + (-3 * 4 + x * 4) = 0

-6 + 2x + (-12 + 4x) = 0

Reorder the terms:

-6 + -12 + 2x + 4x = 0

Combine like terms: -6 + -12 = -18

-18 + 2x + 4x = 0

Combine like terms: 2x + 4x = 6x

-18 + 6x = 0

Solving

-18 + 6x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18' to each side of the equation.

-18 + 18 + 6x = 0 + 18

Combine like terms: -18 + 18 = 0

0 + 6x = 0 + 18

6x = 0 + 18

Combine like terms: 0 + 18 = 18

6x = 18

Divide each side by '6'.

x = 3

Simplifying

x = 3

User Pscheit
by
4.7k points